Oral hydration compared to intravenous hydration in the prevention of post-contrast acute kidney injury in patients with chronic kidney disease stage IIIb: A phase III non-inferiority study (NICIR study). Issue 136 (March 2021) - Sebastià, Carmen; Páez-Carpio, Alfredo; Guillen, Elena; Paño, Blanca; Garcia-Cinca, David; Poch, Esteban; Oleaga, Laura; Nicolau, Carlos
Highlights: Our study showed that the PC-AKI rate of prophylactic oral hydration is non-inferior to that of i.v. hydration in patients with stage IIIb CKD referred for an elective CE-CT. In outpatients with stage IIIb CKD referred for CE-CT, oral hydration prophylaxis is a safe and easy-to-administer alternative in the prevention of PC-AKI. Our study observed no severe hydration-related adverse effects in either the oral or intravenous hydration arm. We also did not report the need for hemodialysis in either study arm. Abstract: Objective: To evaluate the non-inferiority of oral hydration compared to intravenous (i.v.) hydration in the prevention of post-contrast acute kidney injury (PC-AKI) in patients with stage IIIb chronic kidney disease (CKD) referred for an elective contrast-enhanced computed tomography (CE-CT). Material and Methods: This is a prospective, randomized, phase 3, parallel-group, open-label, non-inferiority trial. Patients were randomly assigned 1:1 to receive prophylaxis against PC-AKI either with oral hydration: 500 mL of water two hours before and 2000 mL during the 24 h after performing CE-CT or i.v. hydration: sodium bicarbonate (166 mmol/L) 3 mL/kg/h starting one hour before and sodium bicarbonate (166 mmol/L) 1 mL/kg/h during the first hour after CE-CT. 100 mL of non-ionic iodinated contrast was administered in all cases. The primary outcome was the proportion of PC-AKI in the first 48–72 h after CE-CT. Secondary outcomes were persistent PC-AKI, the need for hemodialysis, and the occurrence of adverse events related to prophylaxis. Results: Of 264 patients randomized between January 2018 and January 2019, 114 received oral hydration, and 114 received i.v. hydration and were evaluable. No significant differences were found (p > 0.05) between arms in clinical characteristics or risk factors. PC-AKI rate was 4.4 % (95 %CI: 1.4−9.9 %) in the oral hydration arm and 5.3 % (95 %CI: 2.0−11.1%) in the i.v. hydration arm. The persistent PC-AKI rate was 1.8 % (95 %CI: 0.2−6.2 %) in both arms. No patient required dialysis during the first month after CE-CT or had adverse effects related to the hydration regime. Conclusion: In those with stage IIIb CKD referred for an elective CE-CT, we provide evidence of non-inferiority of oral hydration compared to i.v. hydration in the prevention of PC-AKI.